Design and development of an algorithm for a take-off performance monitor - Zammit-Mangion, David (Cranfield University, 2001)
A take-off performance monitor is an instrument that is intended to monitor the progress of the take-off manoeuvre in real-time in order to ensure that the aircraft will meet the various distance constraints of the airfield. Several designs have to date been proposed but none have been successful commercially. This work has involved the development of a novel design concept based on the consideration of the time history of the run to obtain an accurate prediction of the distance required to VI. Scheduled post-VI distances are then allowed for in the estimate of the actual distances required to complete the manoeuvre. A performance standard complementing SAE aerospace standard AS-8044 has also been established to ensure system reliability during operation. The algorithms developed were validated using the College of Aeronautics' Jetstream-100 flying laboratory and take-off data of B747 and B737 aircraft. A fixed-base simulator was also used to evaluate the algorithm in adverse operating conditions. The algorithm was demonstrated to meet the named performance standards and is shown to have the potential of being utilised in a successful commercial performance monitor. A novel display design concept is also proposed, providing a basis on which an attractive display can be further developed.